Dinamika Fungsi Masjid di Indonesia: Dari Lokus Pengajaran Islam Ke Pemberdayaan Sosial Ekonomi Umat - Mustain Mustain (UIN Mataram, 2023)
This article explores the evolution of mosque functions, tracing its development from the Golden Age of Islam in the Middle East to its influence on the early phases of Islam in the archipelago, and its contemporary significance for Indonesian society. Employing a historical approach, the paper delineates the transformation of the mosque's role, transitioning from its traditional emphasis on education to a pivotal role in enhancing the social and economic well-being of Muslims. The study's findings indicate that, beyond its primary function as a place of worship, the mosque has evolved into a hub for providing social and economic services to its worshippers, representing a notable departure from its historical role. This article provides a comprehensive understanding of the importance of reassessing the relevance and role of mosques in meeting the multifaceted needs of Muslims. It stands as a crucial focal point for revitalizing the role of the mosque in response to socio-economic sustainability and contemporary societal demands. Abstrak: Artikel ini mengeksplorasi evolusi fungsi masjid, menelusuri perkembangannya dari Zaman Keemasan Islam di Timur Tengah hingga pengaruhnya terhadap fase awal Islam di Nusantara, dan signifikansi kontemporernya bagi masyarakat Indonesia. Dengan menggunakan pendekatan historis, penelitian ini menggambarkan transformasi peran masjid, dari penekanan tradisionalnya pada pendidikan menjadi peran penting dalam meningkatkan kesejahteraan sosial dan ekonomi umat Islam. Temuan penelitian ini menunjukkan bahwa, di luar fungsi utamanya sebagai tempat ibadah, masjid telah berevolusi menjadi pusat untuk menyediakan layanan sosial dan ekonomi bagi para jamaahnya, yang mewakili perubahan penting dari peran historisnya. Artikel ini memberikan pemahaman yang komprehensif tentang pentingnya menilai kembali relevansi dan peran masjid dalam memenuhi berbagai kebutuhan umat Islam. Artikel ini menjadi titik fokus penting untuk merevitalisasi peran masjid dalam menanggapi keberlanjutan sosial-ekonomi dan tuntutan masyarakat kontemporer.